The impact of entrepreneurial leadership on team climate and innovation work behaviour in start-up contexts - NEO, Kin Kah (Institutional Knowledge at Singapore Management University, 2019)
Achieving start-up success is a multi-dimensional challenge. Against this background, this research centres around the experiences gained at an Asian University with a postgraduate Master of Science in Innovation program (MI) aimed at creating novel and viable business ventures as part of so-called Capstone Projects. Given concerns about the - at times - somewhat mediocre nature of ideation and business model creation outcomes of some of the students’ capstone projects in contrast to a couple of very successful, award-winning innovation projects, emphasis was put on identifying and understanding the type of leadership that drives high-quality new ventures, namely entrepreneurial leadership. Other critical factors for start-up success were identified and analysed through mixed method research: entrepreneurial self-efficacy, team climate and the appreciation of age diversity. Based on semi-structured interviews with MI graduates, a conceptual model was developed to examine the interrelatedness of entrepreneurial leadership impact and the critical factors mentioned above. This was followed by a survey questionnaire to gather data on MI graduates aimed at empirically testing the conceptual model and its hypotheses. In the empirical test, entrepreneurial leadership was significantly associated with team climate. The study results suggest that team climate mediates the effect of entrepreneurial leadership impact on innovation work behaviour. This finding helps to understand how effective leaders operate and succeed in a start-up environment. Start-up innovation teams are small and constrained by limited resources. The team climate plays an important role in these innovation teams. In a diverse innovation team, team members often get into heated arguments during business discussions resulting in negative team climate. Strong entrepreneurial leaders are able to foster a positive team climate that promotes innovation. This research also revealed that age diversity can have a negative impact on team climate, e.g. when members do not appreciate other members who are younger or older. In the context of the surveyed innovation teams, appreciation of age diversity among members was positively associated with a positive team climate. However, the study results also suggest that appreciation of age diversity alone is insufficient to foster innovation work behaviour in a team. Team members require a strong entrepreneurial leader to lead them to innovate, e.g. by transforming innovative ideas into useful applications. Such leaders often have strong entrepreneurial self-efficacy and can empower team members to make innovation work, i.e. entrepreneurial leaders of innovation teams succeed in encouraging team members to seek entrepreneurial goals, stimulating an innovation orientation amongst them, identifying innovation opportunities and so forth. To sum up, this study offers new insights into the type of entrepreneurial leadership required to successfully lead innovation teams in a start-up context in order to exploit related business opportunities.